2009
DOI: 10.1161/circresaha.109.206607
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Remodeling Induced by Mitochondrial Aldehyde Stress Stimulates Tolerance to Oxidative Stress in the Heart

Abstract: Rationale: Aldehyde accumulation is regarded as a pathognomonic feature of oxidative stress-associated cardiovascular disease. Objective: We investigated how the heart compensates for the accelerated accumulation of aldehydes. Methods and Results: Aldehyde dehydrogenase 2 (ALDH2) has a major role in aldehyde detoxification in the mitochondria, a major source of aldehydes. Transgenic (Tg) mice carrying an Aldh2 gene with a single nucleotide polymorphism (Aldh2*2) were developed. This polymorphism has a dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 46 publications
(44 reference statements)
8
116
0
Order By: Relevance
“…Another study reported that the dynamic expression of ALDH1B1 correlated with granulocytic development of hematopoietic stem cells; in this report, the author proposed a possible role of ALDH1B1 in retinoic acid metabolism mediating the effect (Luo et al, 2007). A transgenic mouse line having forced expression of the human ALDH2*2 variant exhibited distinct phenotypes, including small body size, reduced muscle mass, diminished fat content, and osteopenia (Endo et al, 2009), all of which are absent from ALDH2-null mice (Yu et al, 2009). One hypothesis to explain such a discrepancy is that the ALDH2*2 mutant subunit not only inactivates the ALDH2 wild-type subunit but also inactivates other ALDHs by forming heterotetramers, thereby blocking their functions.…”
Section: Initial Characterization Of Human Aldh1b1mentioning
confidence: 85%
“…Another study reported that the dynamic expression of ALDH1B1 correlated with granulocytic development of hematopoietic stem cells; in this report, the author proposed a possible role of ALDH1B1 in retinoic acid metabolism mediating the effect (Luo et al, 2007). A transgenic mouse line having forced expression of the human ALDH2*2 variant exhibited distinct phenotypes, including small body size, reduced muscle mass, diminished fat content, and osteopenia (Endo et al, 2009), all of which are absent from ALDH2-null mice (Yu et al, 2009). One hypothesis to explain such a discrepancy is that the ALDH2*2 mutant subunit not only inactivates the ALDH2 wild-type subunit but also inactivates other ALDHs by forming heterotetramers, thereby blocking their functions.…”
Section: Initial Characterization Of Human Aldh1b1mentioning
confidence: 85%
“…Cellular redox homeostasis is maintained by a delicate balance between ROS production and antioxidant defences. 35 When ROS are produced excessively or endogenous antioxidant capacity is diminished, indiscriminate oxidation leads to potentially damaging oxidative stress. The hydroxyl radical (•OH) is a major trigger of the chain reaction forming free radicals, 36 and once occurring on biomembranes, it continues and expands, causing serious cellular damage.…”
Section: Discussionmentioning
confidence: 99%
“…28 Consistent with the mitochondrial localization of the Aldh2*2 protein, levels of 4-HNE adduct proteins were increased in the mitochondrial, but not cytosolic, fraction of Aldh2*2 transgenic (Tg) hearts. Interestingly, despite significant accumulation of 4-HNE adduct proteins in the mitochondrial matrices, left ventricular function in the Aldh2*2 Tg mice was equivalent to that in their wild-type littermates until at least 2 years of age.…”
Section: Cardioprotection Can Be Achieved Within the Setting Of Chronmentioning
confidence: 74%